Chinese medicine PaBing-II protects human iPSC-derived dopaminergic neurons from oxidative stress - Wu, Shouhai; Rong, Cuiping; Lin, Ruishan; Ji, Kaiyuan; Lin, Tongxiang; Chen, Weimin; Mao, Wei; Xu, Yang (Frontiers in Immunology, 2024)
Background PaBing-II Formula (PB-II) is a traditional Chinese medicine for treating Parkinson’s disease (PD). However, owing to the complexity of PB-II and the difficulty in obtaining human dopaminergic neurons (DAn), the mechanism of action of PB-II in PD treatment remains unclear. The aim of this study was to investigate the mechanisms underlying the therapeutic benefits of PB-II in patients with PD. Methods hiPSCs derived DAn were treated with H2O2 to construct the DAn oxidative damage model. SwissTargetPrediction was employed to predict the potential targets of the main compounds in serum after PB-II treatment. Metascape was used to analyze the pathways. Sprague-Dawley rats were used to construct the 6-hydroxydopamine (6-OHDA)-induced PD model, and the duration of administration was four weeks. RNA sequencing was used for Transcriptome analysis to find the signal pathways related to neuronal damage. The associated inflammatory factors were detected by enzyme-linked immunosorbent assay (ELISA). We identified PB-II as an Nrf2 activator using antioxidant-responsive element luciferase assay in MDA-MB-231 cells. Results In vitro experiments showed that the treatment of PB-II-treated serum increased the percentage of TH+ cells, decreased inflammation and the apoptosis, reduced cellular reactive oxygen species, and upregulated the expression of Nrf2 and its downstream genes. Pathway analysis of the RNA-seq data of samples before and after the treatment with PB-II-treated serum identified neuron-associated pathways. In vivo experiments demonstrated that PB-II treatment of PD rat model could activate the Nrf2 signaling pathway, protect the midbrain DAn, and improve the symptoms in PD rats. Conclusion PB-II significantly protects DAn from inflammation and oxidative stress via Nrf2 pathway activation. These findings elucidate the roles of PB-II in PD treatment and demonstrate the application of hiPSC-derived DAn in research of Chinese medicine.